2008
DOI: 10.1007/s00436-008-1168-0
|View full text |Cite
|
Sign up to set email alerts
|

Hysterothylacium aduncum, the only anisakid parasite of sardines (Sardina pilchardus) from the southern and eastern coasts of Spain

Abstract: An epidemiological study was carried out on the anisakids in sardines (Sardina pilchardus) from the southern (Atlantic and Mediterranean) and eastern coasts of Spain. Length of fish was from 12.2-21.0 cm. The anisakids found were identified as the third larval stage (L3) of Hysterothylacium aduncum, with a total prevalence of 11.85%. Prevalence within the host was 9.64% in viscera and 4.69 % in muscle. The highest infection parameters were found in fish from the east coast (western Balearic Sea) with prevalenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
31
2
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 23 publications
6
31
2
1
Order By: Relevance
“…In this way, our results are in accordance with the results found by Abollo, Gestal, and Pascual (2001) for S. pilchardus caught in Galicia (NW Spain) and by Rello et al (2008a) in sardines from the southern and eastern coasts of Spain. However, Sanmartín, Iglesias, Santamarina, Leiro, and Ubeira (1994) found a P of 10% in S. pilchardus from Galicia (NW Spain) higher to the prevalence found by us, probably because the presence of the definitive hosts in waters of NW Spain is higher that in the Mediterranean Sea.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…In this way, our results are in accordance with the results found by Abollo, Gestal, and Pascual (2001) for S. pilchardus caught in Galicia (NW Spain) and by Rello et al (2008a) in sardines from the southern and eastern coasts of Spain. However, Sanmartín, Iglesias, Santamarina, Leiro, and Ubeira (1994) found a P of 10% in S. pilchardus from Galicia (NW Spain) higher to the prevalence found by us, probably because the presence of the definitive hosts in waters of NW Spain is higher that in the Mediterranean Sea.…”
Section: Discussionsupporting
confidence: 95%
“…Accidental human infections with anisakid larvae can occur following the consumption of poorly cooked infected fish and may cause abdominal discomfort and allergy in humans (Audicana et al, 2000;López-Serrano et al, 2000). Despite the commercial and zoonotic importance of larval anisakid infections of fish, their distribution among Spain's Mediterranean teleosts is poorly understood (Rello, Adroher, Benítez, & Valero, 2009;Rello, Adroher, & Valero, 2008a;Valero, López-Cuello et al, 2006;Valero, Martín-Sánchez, Reyes-Muelas, & Adroher, 2000;Valero, Paniagua et al, 2006). The present work reports on the occurrence of larval anisakids in four species of commercial fish caught in the fishing-ground of Tarragona (Mediterranean Sea, NE Spain) and commercialized in the fish market of the abovementioned city.…”
Section: Introductionmentioning
confidence: 97%
“…Many studies were conducted on Anisakidae parasitizing Mediterranean fishes with high commercial value: Greece (Papoutsoglou 1975;Chaligiannisa et al 2012), Spain (Valero et al 2000;Valero et al 2006;Rello et al 2008;Gutiérrez-Galindo et al 2010), Italy (Larizza and Vovlas 1995), Egypt (Morsy et al 2012), and North African central Mediterranean coasts (Farjallah et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study indicated that larger hosts had more infection and parasite load and similarly in a study by Adroher et al (1996) increasing infection levels of H. aduncum were reported in close association with increasing size of horse mackerel. Rello et al (2008) reported increases, though not statistically signifi cant, at prevalence and intensities of infection of H. aduncum by length of Sardina pilchardus from the southern and eastern coasts of Spain. Anderson and Gordon (1982) reported that the higher parasitism observed in larger fi sh over smaller ones might be a result of change in diet of the fi sh and higher activity to search for food.…”
Section: Discussionmentioning
confidence: 99%